Exploration of Students’ Learning Experiences in Developing Creativity through Project-Based Learning - Putri Indah Wahyuningsih; Suci Tuningsih; Nisrina Ajrina Nur Hidayah; Khatmirul Aziz; Heru Siddik Nugroho (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Aim: This study aims to explore students' learning experiences in developing creativity through the implementation of Project-Based Learning (PjBL) in fairy tale learning at the elementary school level. Method: A qualitative approach with a phenomenological method was employed, involving a fourth-grade teacher and fourth-grade students as participants. Data were collected through classroom observations, in-depth interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing, with source and technique triangulation employed to ensure trustworthiness. Result and Discussions: The findings revealed that students' creativity developed progressively throughout the project process, beginning with idea exploration, group discussions, story-planning, revision, and culminating in project presentation. At the beginning of the learning process, students relied heavily on teacher guidance; however, they gradually became capable of independently determining storytelling strategies, modifying storylines, selecting appropriate media, and organizing group roles. The development of creativity was reflected in students' increased ability to generate multiple ideas (fluency), adapt strategies when encountering challenges (flexibility), produce distinctive storytelling performances across groups (originality), and refine their ideas through revision and reflection (elaboration). The study further found that creativity emerged not as an individual process but through the interaction of students' personal experiences, peer collaboration, teacher facilitation, and the use of digital technology as a catalyst for idea generation. Conclusion: These findings suggest that PjBL in fairy tale learning not only produces storytelling products but also creates authentic learning experiences that foster students' creativity in meaningful, contextual, and collaborative ways.